Kalium Sebagai Solusi Hipertensi - Gerardin Ranind Kirana; Reny Nugraheni; Vivien Dwi Purnamasari; Forman Novrindo Sidjabat (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Hypertension is one of the degenerative diseases, where the number of diseases will continue to increase as a person ages. Hypertension itself can cause several complications such as CHD, stroke, kidney failure, diabetes mellitus, and even hypertension can be a factor causing sudden death because sometimes someone who suffers from hypertension does not experience any symptoms. The purpose of community service entitled